Rhizomatic photography:: a proposal for memory cartography (Palíndromo, 2021)
We propose in the article the alignment of rhizome concept of Deleuze & Guattari’s to photogra-phy, understanding it as a possible cultural artifact for cultural studies. Rhizomatic photography is presented as an articulator of history, culture and memory.
Keywords: Rhizome.; Photography.; Cultural studies.; Memory.